P17.05 Hiv test refusals among black africans attending sexually transmitted infection clinics in england, 2013. (13th September 2015) - Mohammed, H; Furegato, M; Nardone, A; Hughes, G
Abstract : Introduction: Black Africans comprise the second largest group affected by HIV in England, but it is estimated that 34% are  undiagnosed. We identified factors associated with HIV test refusals among Black African sexually transmitted infection (STI) clinic attendees. Methods: Data on all STI clinic attendances in England in 2013 were obtained from the genitourinary medicine clinic activity dataset (GUMCADv2). Individuals diagnosed with HIV on or before 31 st December 2012 were excluded from analysis. Ethnic variations in HIV test refusal at an attendance were determined. Further analyses were restricted to Black Africans, and bivariate and multivariate associations between demographic and clinical characteristics and HIV test refusal were assessed. All associations were determined using generalised estimating equations regression and adjusted odds ratios (aORs) with 95% confidence intervals (CIs) are reported. Results: Black Africans made 92, 331 attendances at STI clinics in 2013 and refused an HIV test on 7, 666 (8.3%) occasions. After adjusting for gender/sexual orientation, Black Africans were least likely to have refused an HIV test [aOR (95% CI): 0.503 (0.490–0.517)] ( vs. White British persons). Among Black Africans, the odds of refusing an HIV test decreased with age [0.983 (0.980–0.986)] and were lower among those born outside the UK [0.676 (0.637–0.717)], those who were tested for HIV within the last year [0.802 (0.762–0.845)] and in men who have sex with men [0.307 (0.235–0.402)] ( vs. heterosexual men and all women), while the odds were higher among those diagnosed with a new STI at the same attendance [1.272 (1.193–1.357)]. Conclusion: Among Black Africans, targeted health promotion may be needed to improve HIV testing rates and decrease the proportion undiagnosed, especially for heterosexual men, women, younger, UK-born persons and those newly diagnosed with an STI. Disclosure of interest statement: There are no conflicts of interest.